2010
DOI: 10.1007/s11240-010-9675-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences between hyperhydric and normal in vitro shoots of Handroanthus impetiginosus (Mart. ex DC) Mattos (Bignoniaceae)

Abstract: The anatomy of normal and hyperhydric shoots (leaves and stems) of in vitro Handroanthus impetiginosus was compared using light microscopy, scanning electron microscopy, and transmission electron microscopy. In contrast to normal shoots, hyperhydric shoots presented numerous anatomical abnormalities at the proliferation stage. Disorganized cortex, epidermal holes, epidermal discontinuity, collapsed cells, and other structural characteristics were observed in hyperhydric shoots. So, by using anatomical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 18 publications
(37 reference statements)
3
22
0
1
Order By: Relevance
“…Jausoro et al, (2010) reported disorganized cortex, epidermal holes, epidermal discontinuity, collapsed cells, and other structural characteristics were observed in hyperhydric shoots of Handroanthus impetiginosus.…”
Section: A New Whole Plantmentioning
confidence: 94%
“…Jausoro et al, (2010) reported disorganized cortex, epidermal holes, epidermal discontinuity, collapsed cells, and other structural characteristics were observed in hyperhydric shoots of Handroanthus impetiginosus.…”
Section: A New Whole Plantmentioning
confidence: 94%
“…Anatomical and ultrastructural studies of diverse species that compared hyperhydric and normal in vitrogrown plants have been reported (Picoli et al 2008;Jausoro et al 2010).…”
Section: Alterations In Anatomical and Ultrastructural Of Leaves Incrmentioning
confidence: 99%
“…These conditions may cause increased reserves or biomass accumulation, photosynthesis inhibition, and abnormal stomata development, which can lead to the development of hyperhydricity. Hyperhydricity hinders micropropagation and acclimatization, causing significant plant losses when vitroplants are transferred to ex vitro conditions (Jausoro et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: cluna@agr.unne.edu.ar. Handroanthus impetiginosus have been limited to morphology and physiological aspects during seed germination (Amaral da Silva et al, 2004) and the physiological abnormalities due to hyperhydricity of shoots cultured in vitro (Jausoro et al, 2010). More recently, Larraburu et al (2012) reported a protocol for the micropropagation of H. impetiginosus.…”
Section: Introductionmentioning
confidence: 99%